Analisis Pencemaran Bakteri Di Instalasi Gizi Rumah Sakit Umum Daerah Abdul Wahab Syahranie Samarinda (Jurnal Medika : Karya Ilmiah Kesehatan, 2024)
This study aims to determine the contamination of bacteria in the room, eating and cooking utensils, foodstuffs and food and food handlers. The study was conducted on April 2017 is housed in nutrition installation of RSUD Abdul Wahab Syahranie Samarinda with sample of 12 rooms, 22 of eating and cooking utensils, 25 foodstuffs and food and 35 food handlers. The sampling method was by sampling the material then taken to the laboratory to analyze the germ figures and type of bacteria. The results obtained will be analyzed data in analytic description.Results showed the room air germ number ranges 360​​-more than 1885 CFU/m3, eating and cooking utensils range from 0-102 CFU/ m2, from foodstuffs and food there is only one food containing E. coli is 150 CFU/g and from food handlers did not find any carrier of Salmonella sp. The type of bacteria found in the room, equipment, food and food handlers are Staphylococcus epidermidis, Bacillus sp., Enterobacter sp., Klebsiella sp., Streptococcus faecalis, Pseudomonas sp., Citrobacter sp., Acinetobacter sp., Klebsiella pneumoniae, Citrobacter freundii, Enterobacter agglomeran, Klebsiella oxytoca, Klebsiella ozanae and Staphylococcus non aureus. The results obtained can be concluded that in general table fill the requirements of Kepmenkes No. 1204/Menkes/SK/X/2004.
Keywords: Nutrition Installation; number of airborne germs; eating utensils; food; food handlers; rectal swabs